Analisis Engagement Rate Instagram UMKM Kerajinan Hijau di Indonesia Berdasarkan Format Konten dan Jumlah Follower - Prima Ditahardiyani; Hartoni Hartoni; Karimal Arum Shafriani (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
The growing public awareness of environmental issues has encouraged green craft small and medium enterprises (SMEs) to communicate their sustainability values more effectively through digital media. Instagram is a relevant platform because it can visually convey sustainability messages through photos, videos, and carousels, while allowing audience responses to be measured through engagement rate. However, research on audience engagement among green craft SMEs in Indonesia has yet to be conducted. Therefore, this study aims to measure the engagement rate of Instagram accounts for green craft SMEs, analyze the influence of follower count on engagement rate, and evaluate engagement rates by content format. This study is the first to analyze engagement rates for Instagram accounts of green craft SMEs across content formats and follower counts. The sample consisted of 16 Instagram accounts selected using a purposive sampling method that met the following criteria: producing green craft products, having more than 5,000 followers, and actively posting sustainability-related content. Data were collected from the 30 most recent posts of each account as of July 2025, including follower counts, likes, comments, and content formats such as photos, videos, and carousels. A descriptive, quantitative method was used to measure and evaluate engagement rates by content format, while Spearman’s correlation analysis was applied to examine the influence of follower count on engagement rate. The results show that the average engagement rate of Instagram accounts of green craft SMEs was 2.29%, categorized as moderate; video content generated the highest engagement rate, while follower count did not significantly affect engagement rate. Based on these findings, green craft SMEs are advised to prioritize video content and develop consistent sustainability narratives, while government support can focus on Instagram training that emphasizes sustainability messaging.